Intraabdominal Hemorrhage Due to Spontaneous Rupture of Superior Mesenteric Artery - Onder Ozden; Ender Fakioglu; Murat Alkan; Hilmi Serdar Iskit (Çukurova Üniversitesi Tıp Fakültesi Dergisi, 2014)
Spontaneous rupture of mesenteric vessel is an extremely rare entity in children. We describe a 14-year-old boy who was presented with an acute abdomen and hemorrhagic shock without any history of trauma. Rupture of superior mesenteric artery was found at laparotomy. An attempt of vascular repair was failed due to vascular fragility. As whole midgut necrosis was developed, extended intestinal resection from 3th duodenal segment to descending colon and closure of duodenal and colonic ends were performed. Abdominal compartment syndrome, duodenal fistula and sepsis were encountered as major postoperative complications during his early postoperative period. Both abdominal compartment syndrome and duodenal fistula ceased after three weeks. Diagnosis of Ehlers Danlos Syndrome Type IV could be established according to his specific facial features, thin translucent skin, propensity to bleeding, rupture of mesenteric vessel and histopathological findings. Total parenteral nutrition was applied for energy requirement . A spontaneous femoral arteriovenous fistula was developed at the third month which was managed conservatively. He died 5 months later, while waiting for intestinal transplant. Ehlers Danlos Type IV diagnosis without any identical vascular lesion was also verified in his twin brother. Ehlers Danlos Syndrome Type IV should be kept in mind in cases of abdominal apoplexy. Repair of vascular complications could be impossible due to abnormal type III collagen leaded vascular fragility. [Cukurova Med J 2014; 39(2.000): 408-411]